DISTANCE LEARNING OF FOREIGN LANGUAGES - Gulayim Erjanbaeva (Journals Park Publishing, 2022)
This article provides information on the forms and methods of teaching foreign languages in educational institutions. There are also modern requirements for distance learning of foreign languages in the field of education and recommendations for conducting lessons.
Keywords: Distance education; foreign languages; education system